2018
DOI: 10.1111/aos.13943
|View full text |Cite
|
Sign up to set email alerts
|

Impact of donor tissue diameter on postoperative central endothelial cell density in Descemet Membrane Endothelial Keratoplasty

Abstract: Purpose To assess the effect of donor tissue diameter in Descemet Membrane Endothelial Keratoplasty (DMEK) on postoperative endothelial cell density (ECD) mainly in Fuchs Endothelial Corneal Dystrophy (FECD) patients. Methods Retrospective review of 693 consecutive DMEK surgeries from the prospective Cologne DMEK database performed between 07/2011 and 07/2016 at the Department of Ophthalmology, University of Cologne. Eight‐ versus ten‐millimetre large donor DMEK grafts of two different surgeons using identical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 27 publications
(52 reference statements)
1
9
1
Order By: Relevance
“…Although patients with BK should have few healthy endothelial cells in the peripheral cornea, most patients with FECD might have some healthy endothelium in the peripheral cornea [21]. This difference of healthy endothelium distribution between BK and FECD may be one of the reasons why the results of the current study differed from those of Schrittenlocher et al [17]. Although detailed knowledge regarding the migration of corneal endothelial cell is lacking, it is considered that corneal endothelial cells close the wound gap mainly via migration and increased cell spreading [22].…”
Section: Plos Onecontrasting
confidence: 66%
See 1 more Smart Citation
“…Although patients with BK should have few healthy endothelial cells in the peripheral cornea, most patients with FECD might have some healthy endothelium in the peripheral cornea [21]. This difference of healthy endothelium distribution between BK and FECD may be one of the reasons why the results of the current study differed from those of Schrittenlocher et al [17]. Although detailed knowledge regarding the migration of corneal endothelial cell is lacking, it is considered that corneal endothelial cells close the wound gap mainly via migration and increased cell spreading [22].…”
Section: Plos Onecontrasting
confidence: 66%
“…In contrast, Schrittenlocher et al reported that postoperative ECD was not significantly associated with DMEK graft diameters in the range of 8-10 mm in FECD eyes. [17]. Although many studies have evaluated graft size, no study has evaluated the ratio of graft to cornea area.…”
Section: Plos Onementioning
confidence: 99%
“… 14 Conversely, the study from Europe reported that postoperative ECD was not significantly associated with DMEK graft sizes in the range of 8–10 mm in FECD cases with healthy peripheral host endothelium. 36 This is likely due to smaller eyeballs with shallower anterior chambers in Asians, causing smaller graft sizes used in our study (7.0–8.5 mm) and Japanese study (5.0–8.5 mm). 14 More importantly, advanced FECD and bullous keratopathy account for higher proportion of EK cases in Asia.…”
Section: Discussionmentioning
confidence: 68%
“…Corneal endothelial cell density (ECD) is higher in the periphery compared to the central cornea, especially beyond 9.00 mm [27,28]. Delivering larger grafts could theoretically not only provide a higher number of transplanted cells but also include an area containing cells with high proliferative potential, which could potentially increase graft survival [29][30][31].…”
Section: Graft Sizementioning
confidence: 99%